Effect of chopping time and heating on 1 H nuclear magnetic resonance and rheological behavior of meat batter matrix - Zhou, Fen; Dong, Hui; Shao, Jun‐Hua; Zhang, Jun‐Long; Liu, Deng‐Yong (Animal science journal, 2018)
The effect of chopping time and heating on physicochemical properties of meat batters was investigated by low‐field nuclear magnetic resonance and rheology technology. Cooking loss and L* increased while texture profile analysis index decreased between chopping 5 and 6 min. The relaxation time T 21 (bound water) and its peak area ratio decreased, while the ratio of T 22 peak area (immobilized water) in raw meat batters gradually increased with the extension of chopping time. However, T 22 was opposite after being heated and a new component T 23 (free water) appeared (T 2i is the spin – spin relaxation time for the ith component.). The initial damping factor (Tan δ) gradually decreased and there were significant difference between 4 and 5 min of chopping time. There were significantly positive correlations between the ratio of peak area of T 22 and chopping time, the storage modulus (G′), cooking loss, and L* , respectively. Continued chopping time could improve the peak area proportion of T 22 in raw meat batters. Further, the higher the peak area proportion of T 22 in raw meat batters, the cooking loss of heated meat gel was higher. Also, the stronger the mobility of immobilized water in meat batter, the higher the L* of the fresh meat batters. Thus, it is revealed that the physicochemical properties of meat batter are significantly influenced by chopping time which further affects the water holding capacity and the texture of emulsification gel.